Design and production of sustainable lightweight concrete precast sandwich panels for non-load bearing partition walls. Issue 1 (1st January 2021) - Moutassem, Fayez; Al Amara, Kadhim
Abstract: The trend for utilizing sustainable products is becoming increasingly important in the construction industry. Precast concrete sandwich systems containing expanded polystyrene (EPS) is gradually replacing the conventional blockwork systems due to its lightweight, enhanced insulation properties and rapid installation. Accordingly, there is a need to optimize the design and production of this system to provide superior insulation, durability and rapid installation while ensuring adequate bonding, strength and mechanical properties to sufficiently fit its purpose. Research has shown that the system's technical properties are highly dependent on the mix design and the production and installation methods. This study involved the design and production of a sustainable lightweight precast concrete sandwich panel for non-load bearing partition wall systems. An experimental program was developed to identify the optimum mixture proportions for the EPS concrete core. Practical procedures for system production and installation were proposed. Physical and mechanical properties for the proposed EPS concrete system were determined based on experimental testing and calculations. A relationship between the plastic density of fresh EPS concrete and its compressive strength was established to ensure quality control before concrete is cast. Results revealed a high degree of correlation of 0.97 between the core density and compressive strength. Technical comparison revealed that the proposed system is superior in comparison to the conventional lightweight blockwork system. Furthermore, the installation time for the proposed partition wall system was 3 times faster in comparison with the conventional block work system, which would lead to significant reduction in the total cost.